Vocational Training Students’ Self-Assessment in Higher Education - Kiss, Zsuzsanna; Barizsné Hadházi, Edit (International Journal of Engineering and Management Sciences, 2017)
This paper is intended to clarify the phenomenon that lower achieving students tend to evaluate their own academic performance less accurately than those who are better in their studies. Former studies have found that lower performers generally overestimate while higher performers underestimate their performance. The current study analyses the self-assessment behaviour and efficiency among Hungarian higher vocational education students. We found that the lowest level of higher education students typically overestimate themselves. Over results strengthen the empirical evidences in former studies that higher-achieving students evaluate their performance more accurately than their lower achieving fellows. Furthermore we found that lower-achieving students tend to evaluate their performance less accurate and typically over-assess their examination results than high-achieving students, who generally evaluate themselves more accurate and rather underestimate. We analysed the difference between the two genders too. Compared to female students, male tend to evaluate their results more accurate and overestimate their own performance more.